Pemberdayaan Karang Taruna dalam Sirkular Ekonomi Pengelolaan Sampah dan Pertanian Organik Skala Rumah Tangga - Pasasa, Linus; Alamta Singarimbun; Wahyudi Parnadi (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2025)
This community service program aims to empower local community partnerships by equipping residents with knowledge and problem-solving skills that are comprehensive, meaningful, thorough, and sustainable. It does so through the application of the circular economy concept, which seeks to extend the life cycle of products, raw materials, and available resources so that they can be used for as long as possible. This concept emphasizes the importance of conserving resources by reducing waste and recycling materials after their use, thereby creating a sustainable loop. It is an innovative approach that not only has the potential to reduce negative environmental impacts but also opens new economic opportunities through the development of sustainable businesses. The target partner of this program is the economically unproductive youth community group Karang Taruna PAKUPAYUNG, located in Pasirlayung Urban Village, Cibeunying Kidul District, Bandung City. The objective of this community engagement initiative is to empower Karang Taruna PAKUPAYUNG by utilizing plastic recycling within the framework of a circular economy in household-scale waste management and organic farming. The ultimate goal is to achieve zero waste and support food security in the Pasirlayung community. The results of the analysis indicate a significant increase in knowledge among the Karang Taruna PAKUPAYUNG members regarding "Zero Waste Management" and household-scale organic farming.    Abstrak Kegiatan pengabdian masyarakat ini bertujuan untuk pemberdayaan kemitraan masyarakat dengan cara membekali masyarakat pengetahuan dan keterampilan yang problem solving, komprehensif, bermakna, tuntas dan berkelanjutan, melalui penerapan konsep sirkular ekonomi yang berupaya memperpanjang siklus hidup dari suatu produk, bahan baku, dan sumber daya yang ada agar dapat dipakai selama mungkin. Konsep ini menekankan pentingnya menjaga sumber daya dengan cara mengurangi limbah, mendaur ulang kembali setelah masa pakai mereka berakhir, menciptakan lingkaran yang berkelanjutan. Ini adalah pendekatan inovatif yang tidak hanya berpotensi mengurangi dampak lingkungan negatif, tetapi juga dapat membuka peluang ekonomi baru melalui pengembangan bisnis yang berkelanjutan. Mitra sasaran masyarakat dari kegiatan ini adalah masyarakat yang tidak produktif secara ekonomi yaitu Karang Taruna PAKUPAYUNG, Kel. Pasirlayung, Kec.Cibeunying Kidul Kota Bandung. Tujuan program pengabdian masyarakat ini adalah pemberdayaan karang taruna PAKUPAYUNG dalam memanfaatkan daur ulang plastik dalam konteks sirkular ekonomi pengelolaan sampah dan pertanian organik skala rumah tangga untuk mewujudkan zero waste dan mendukung ketahanan pangan di kelurahan Pasirlayung kota Bandung. Hasil analisis menunjukkan bahwa terjadi peningkatan pengetahuan tentang “Zero Waste managemen” Karang Taruna PAKUPAYUNG dan pertanian organik skala rumah tangga.